2020
DOI: 10.1101/2020.07.23.218164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genetic architecture of the sexually selected sword ornament and its evolution in hybrid populations

Abstract: Biologists since Darwin have been fascinated by the evolution of sexually selected ornaments, particularly those that reduce viability. Uncovering the genetic architecture of these traits is key to understanding how they evolve and are maintained. Here, we investigate the genetic architecture of a sexually selected ornament, the “sword” fin extension that characterizes many species of swordtail fish (Xiphophorus). Using sworded and swordless sister species of Xiphophorus, we generated a mapping population and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…Our QTL analysis, consistent with earlier genetic findings [41], uncovered that several chromosomal regions contribute to the polygenic basis of the male structure. Consistently, the major locus on chromosome 13 fully overlaps a similar broad QTL that was obtained in an independent study for the character sword length in natural hybrids between a swordless (X. birchmanni) and a sworded (X. malinche) Northern swordtail species [48].We identified two candidate genes that appear to be involved in the development of the sword. Rather than being typical regulators of development and differentiation such as transcription factors or extracellular diffusible growth factors, experiments identified a channel protein, kcnh8, and a chaperone, fkpb9.…”
Section: Discussionsupporting
confidence: 82%
“…Our QTL analysis, consistent with earlier genetic findings [41], uncovered that several chromosomal regions contribute to the polygenic basis of the male structure. Consistently, the major locus on chromosome 13 fully overlaps a similar broad QTL that was obtained in an independent study for the character sword length in natural hybrids between a swordless (X. birchmanni) and a sworded (X. malinche) Northern swordtail species [48].We identified two candidate genes that appear to be involved in the development of the sword. Rather than being typical regulators of development and differentiation such as transcription factors or extracellular diffusible growth factors, experiments identified a channel protein, kcnh8, and a chaperone, fkpb9.…”
Section: Discussionsupporting
confidence: 82%
“…This can result in an incompatibility generated by misregulation and transgressive expression of such genes in hybrids. ( A ) tspan8 (left) and pkma (right) are examples of genes for which swordtail hybrids exhibit low and high misexpression, respectively (MM: X. malinche ; BB: X. birchmanni ; MB: F 1 hybrids; data from Powell et al, 2021 ). ( B ) This simplified diagram illustrates how mismatches in co-evolved regulatory elements can cause misexpression.…”
Section: From Pattern To Process: Genome Evolution After Hybridization Is Shaped By Diverse Evolutionary Forcesmentioning
confidence: 99%
“…As expected from the cross design, average ancestry across ancestry informative sites in our dataset of 943 males and females indicated that on average 50% of the genome was derived from each parental species. Our previously published dataset for QTL mapping included 568 males [66].…”
Section: Identifying Loci Under Selection Using Controlled Crosses and Natural Populationsmentioning
confidence: 99%
“…We also recently generated a large mapping panel of F2 hybrids between X. birchmanni ´ X. malinche, which we used for QTL mapping of male sexually selected traits [66]. Here, we reanalyzed this mapping panel, doubling our sample size by including females, to identify strong segregation distorters.…”
Section: Identifying Loci Under Selection Using Controlled Crosses and Natural Populationsmentioning
confidence: 99%